Evolution of Action Potential Alternans in Rabbit Heart during Acute Regional Ischemia. (26th February 2015) - Martišienė, Irma; Jurevičius, Jonas; Vosyliūtė, Rūta; Navalinskas, Antanas; Treinys, Rimantas; Mačianskienė, Regina; Benetis, Rimantas; Matiukas, Arvydas; Pertsov, Arkady M.
Abstract : This study investigates the development of the spatiotemporal pattern of action potential alternans during acute regional ischemia. Experiments were carried out in isolated Langendorff-perfused rabbit heart using a combination of optical mapping and microelectrode recordings. The alternans pattern significantly changed over time and had a biphasic character reaching maximum at 6–9 min after occlusion. Phase I (3–11 minutes of ischemia) is characterized by rapid increase in the alternans magnitude and expansion of the alternans territory. Phase I is followed by gradual decline of alternans (Phase II) in both magnitude and territory. During both phases we observed significant beat-to-beat variations of the optical action potential amplitude (OAPA) alternans. Simultaneous microelectrode recordings from subepicardial and subendocardial layers showed that OAPA alternans coincided with intramural 2 : 1 conduction blocks. Our findings are consistent with the modeling studies predicting that during acute regional ischemia alternans can be driven by 2 : 1 conduction blocks in the ischemic region.